Peningkatan Kompetensi Digital Marketing Program Kewirausahaan Batik Poetra Dolokgede di Kabupaten Bojonegoro Melalui Kegiatan “Sinau Bareng” Ademos Indonesia - Jokhanan Kristiyono; Dian Eka Safitri; Agis Savira N U; Trivenadyah Nurmala; Kartika Cahya Jauhariya; Hilda Kurniawati P (LPPM Stikosa - AWS, 2023)
The problem of poverty and population development is still a crucial social issue in Bojonegoro district during technological development issue. As a non-governmental organization, Ademos Indonesia contributes together with local actors of small-medium enterprises (SME) in Indonesia called UMKM in developing their potential. Through research-based community service activities with the theme